2004
DOI: 10.1196/annals.1307.055
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Babesia bigemina Infection in Pregnant Cows

Abstract: Babesiosis is a tick-borne disease of cattle caused by Babesia bigemina and Babesia bovis and is transmitted by the tick vector Boophilus microplus. In this study, we investigate B. bigemina infection regarding the clinical infection, T cell distribution, and cytokine profile during the acute phase of an experimental infection in pregnant cows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Similar observations were noticed by Garcia et al (12), who showed that in cattle infected with Babesia bigemina, in contrast to in vitro conditions (7,8), no differences were observed in the levels of CD4+ and CD8+ lymphocytes in comparison with the healthy animals.…”
Section: Discussionsupporting
confidence: 90%
“…Similar observations were noticed by Garcia et al (12), who showed that in cattle infected with Babesia bigemina, in contrast to in vitro conditions (7,8), no differences were observed in the levels of CD4+ and CD8+ lymphocytes in comparison with the healthy animals.…”
Section: Discussionsupporting
confidence: 90%
“…(16) showed that induction of the IL10 message in the spleen was followed by reduced levels of IL12, IFNγ and TNFα expression and that IL10 production was associated with the higher susceptibility to B. bovis of adult cattle compared with calves. The immune responses of cattle, during infection by B. bigemina , predominantly involved a Th1 response associated with the detection of IFNγ, TNFα and iNOS and no or weak detection of IL4 and IL10 (25). In our study, IFNγ production was not detected in PBMC supernatant from Babesia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Anaplasma, Babesia, Ehrlichia and Theileria species are the most important tick-borne haemoparasites to livestock and wildlife worldwide (Kettle 1995;Sparagano et al 1999;Grootenhuis 2000;Steyl et al 2003;Nijhof et al 2003;Penzhorn 2006). The pathogenesis, immunology and pathological effects to susceptible animals have been extensively described (Morzaria 1989;Kettle 1995;Chansiri et al 1999;Grootenhuis 2000;Homer et al 2000;Nijhof et al 2003Nijhof et al , 2005Garcia et al 2004;Kocan et al 2004). …”
Section: Introductionmentioning
confidence: 96%